Employee Professional Development and Improving Organizational Effectiveness: Exploring the Impact of HR Policies on Employee Professional Development (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Professional development is a planned program of activities and events that provides for and contributes to the personal and professional improvement of employees. Professional development opportunities are for all employees in all job categories. In the past decades development of information technologies, increased international competition on the free market, globalization and businesses expanding outside of their countries of origin have led to significant changes in the societies all over the world. All these changes and the world economic and social crisis have to be changed in the demographical structure of the work force, raising the issue of engaging human resources, especially employee, into social and economic development. Responding to these changes and aiming to create a high level of competence, organizations today face the challenge of incorporating diversity management. Human resource management, through its policies and procedures based on diversity management, can recruit, motivate, develop and retain talented employees for all social groups, especially employee. The aim of this study is to present and analyze how policies and procedure developed by the human resources management influence professional development and promotion of employee in organizations. The study will especially analyze four types of policies and procedures: equal opportunities, development possibilities, formalizing the human resources management system and work-life balance and their influence on professional development of employee in organizations. At the end, the study will present potential avenues of further research in this field.